2022
DOI: 10.3390/pr10020405
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Four Inert Powders on the Minimum Ignition Energy of Sucrose Dust

Abstract: In order to evaluate the effect of inert powder on the ignition sensitivity of sucrose dust, this study investigated the effects of NaHCO3, NaCl, NH4H2PO4 and Al(OH)3 on the minimum ignition energy (MIE) of sucrose dust. The results showed that all four different inert powders inhibited the MIE of sucrose dust, and all of them showed a trend that the smaller the particle size of the inert powders, the better the inhibition effect. The inhibition effect was ranked as NaHCO3 > NH4H2PO4 > NaCl > Al(OH)3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…The study also found that different types of inert dust have different explosion suppression effects, but the cost of inert dust also needs to be considered when selecting an efficient inert dust to suppress explosions. Even for the same type of inert dust, if its particle size, degree of dispersion, humidity, and spreading range are different, the effect of suppressing explosions is also different [25][26][27][28][29] . Inert dust with better explosion suppression effect usually not only does not participate in the explosion, but also absorb heat during the suppression process, and can release some gases and solid products that help to suppress the explosion, so as to achieve better explosion suppression effect 30,31 .…”
Section: Openmentioning
confidence: 99%
“…The study also found that different types of inert dust have different explosion suppression effects, but the cost of inert dust also needs to be considered when selecting an efficient inert dust to suppress explosions. Even for the same type of inert dust, if its particle size, degree of dispersion, humidity, and spreading range are different, the effect of suppressing explosions is also different [25][26][27][28][29] . Inert dust with better explosion suppression effect usually not only does not participate in the explosion, but also absorb heat during the suppression process, and can release some gases and solid products that help to suppress the explosion, so as to achieve better explosion suppression effect 30,31 .…”
Section: Openmentioning
confidence: 99%
“…After that, the flame temperature will rise rapidly [14]. During the emergence and propagation of the flame, heat transfer plays a major role [16]. After the explosion, the explosion pressure can be reckoned according to the residual gas of the explosive reaction [13].…”
Section: Introductionmentioning
confidence: 99%